Strengthen the Mainstreaming of Religious Moderation in Higher Education Through Certification Agency - Ahmad Fawaid; Windi Astutik (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Universities are the main target of the spread of Radical Islam among the Youth. Even though regulations have been set by the government to apply national insights, the practice of implementing them in universities is not optimal. This research aims to explore the practice of religious certification to support national beliefs, moderation, and religious harmony. This research was conducted at Nurul Jadid University, one of the Islamic boarding schools in the Probolinggo region, East Java. In responding to the regulatory policy of implementing nationalism in higher education, Nurul Jadid University established a Religious Certification Institution which functions to carry out standardization of religious needs which include the Koran, furūḍ al-‘Ainiyyah, religious teachings and Islamic boarding schools. By using a qualitative paradigm with a semi-structured interview approach and field observations, this research shows that the religious certification program as the mainstreaming of religious moderation for students at Nurul Jadid University is very effective in educating students of moderation and tolerance. In addition, this study found that religious certification was used as a certificate accompanying a diploma (SKPI) whose legality was recognized by Permendikbudristek No. 6 of 2022 concerning Diplomas, Competency Certificates, Professional Certificates, Degrees, and the Equivalence of Diplomas of Higher Education in Other Countries to support student competence and prove that UNUJA alumni are moderate cadres.